Sprint running: how changes in step frequency affect running mechanics and leg spring behaviour at maximal speed - Monte, A.; Muollo, V.; Nardello, F.; Zamparo, P. (Journal of Sports Sciences, 2017)
The purpose of this study was to investigate the changes in selected biomechanical variables in 80-m maximal sprint runs while imposing changes in step frequency (SF) and to investigate if these adaptations differ based on gender and training level. A total of 40 athletes (10 elite men and 10 women, 10 intermediate men and 10 women) participated in this study; they were requested to perform 5 trials at maximal running speed (RS): at the self-selected frequency (SFs) and at SF ±15% and ±30%SFs. Contact time (CT) and flight time (FT) as well as step length (SL) decreased with increasing SF, while kvert increased with it. At SFs, kleg was the lowest (a 20% decrease at ±30%SFs), while RS was the largest (a 12% decrease at ±30%SFs). Only small changes (1.5%) in maximal vertical force (Fmax) were observed as a function of SF, but maximum leg spring compression (?L) was largest at SFs and decreased by about 25% at ±30%SFs. Significant differences in Fmax, Delta y, kleg and kvert were observed as a function of skill and gender (P < 0.001). Our results indicate that RS is optimised at SFs and that, while kvert follows the changes in SF, kleg is lowest at SFs.